Specimen Size Effect on Bend Properties of Molybdenum Doped with Potassium-Silicate - Hiraoka, Y.; Hoshika, T.; Yoo, M.K.; Choi, J. (1995)
In order to investigate the effect of specimen size on the strength and the ductility of molybdenum, bend angles at temperatures between liquid nitrogen temperature and room temperature were carried out for the recrystallized sheet of molybdenum doped with pottasium-silicate. In this study the low-temperature fracture strength and ductility of the material were represented by critical stress and critical temperature, respectively. The results are summarized as follows. (1) As the specimen width decreased from 4mm to 1mm with the specimen thickness being 1mm, the critical stress tended to increase whilst the yield strength was almost unchanged. (2) Increase of the critical stress with decreasing the specimen width was related with the crack generation and propagation characteristics. The size of the crack generation site tended to be smaller, as the specimen width decreased. (3) The critical temperature tended to decrease as the specimen width decreased. This result was attributed mainly to the increase of the critical stress. ？ 1995, Japan Society of Powder and Powder Metallurgy. All rights reserved.